1987
DOI: 10.1111/j.1529-8817.1987.tb04221.x
|View full text |Cite
|
Sign up to set email alerts
|

THE RELATIONSHIP BETWEEN VALVE DIAMETER AND NUMBER OF CENTRAL FULTOPORTULAE IN THALASSIOSIRA WEISSFLOGII (BACILLARIOPHYCEAE)1

Abstract: Cells well below the reported minimum size for Thalassiosira weisslogii (Grunow) Fryxell et Hasle were observed in two unialgal cultures. The relationship between diameter and number of central fultoportulae was found to be very regular. Regresion analysis of three different populations showed equivalent slopes and r2 values above 80%. The y‐intercepts were significantly different and support observations in the litrature that nonmarine valeve of T. Weissflogii have fewer central fultoportulae than marine form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…There are many cultural studies investigating the relationship between morphological characteristics and environmental parameters, which reported that the morphological differences may be dependent on the environmental parameters e.g. salinity (Johansen & Theriot, 1987;Wendker & Geissler, 1988;Trobajo et al, 2004a;Trobajo et al, 2004b, Trobajo et al, 2011. In these studies, it is mentioned that valve length increases with higher salinity, while contrastingly, valve width decreases with high salinity (Trobajo et al, 2004a) in spite of this; valve width was also reported increase with increasing salinity (Cox, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…There are many cultural studies investigating the relationship between morphological characteristics and environmental parameters, which reported that the morphological differences may be dependent on the environmental parameters e.g. salinity (Johansen & Theriot, 1987;Wendker & Geissler, 1988;Trobajo et al, 2004a;Trobajo et al, 2004b, Trobajo et al, 2011. In these studies, it is mentioned that valve length increases with higher salinity, while contrastingly, valve width decreases with high salinity (Trobajo et al, 2004a) in spite of this; valve width was also reported increase with increasing salinity (Cox, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Conticribra guillardii has 0-4 randomly distributed valve face fultoportulae (Hasle 1978), whereas C. weissflogii has many valve face fultoportulae arranged in a slightly irregular ring pattern within the subcentral area (Fryxell & Hasle 1977). The number and position of the subcentral fultoportulae in C. weissflogii have been shown to vary according to the diameter of valve and salinity (e.g., Johansen & Theriot 1987) and also to various cultural conditions such as deficiency of nutrient (Kang et al 1996). Nevertheless, the variation of valve face fultoportulae represents a distinguishing character for C. weissflogii (Fryxell & Hasle 1977), because no other species shows this pattern of fultoportulae.…”
Section: Introductionmentioning
confidence: 99%
“…salinity (Johansen & Theriot, 1987;Wendker & Geissler, 1988;Trobajo et al, 2004a;Trobajo et al, 2004b, Trobajo et al, 2011. In these studies, it is mentioned that valve length increases with higher salinity, while contrastingly, valve width decreases with high salinity (Trobajo et al, 2004a) in spite of this; valve width was also reported increase with increasing salinity (Cox, 1995).…”
Section: Discussionmentioning
confidence: 94%